PEMBERIAN MASKER GRATIS SEBAGAI LANGKAH PREVENTIF TERHADAP DAMPAK SERIUS POLUSI UDARA DI JAKARTA - Herzani, Adinda; Wijoyo, Amin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
This research analyzes the health and economic impacts of air pollution in Jakarta Province, Indonesia, with a focus on the initiative to provide free masks as a preventive measure. In dealing with high levels of air pollution, the methods used include analysis of study areas, evaluation of exposure data, production of campaign videos to care about air pollution, and distribution of free masks. Specific findings demonstrate the significant impact of air pollution on public health, especially on respiratory diseases and the economic burden it causes. The initiative to provide free masks is a concrete step in protecting public health from air pollution. The community's positive response shows the potential long-term impact on environmental awareness and health. This article emphasizes the importance of preventive efforts based on understanding the health and economic impacts of air pollution, which not only provide short-term protection but also raise awareness of environmental and health problems in the long term.